2011
DOI: 10.1016/j.jchromb.2011.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the LC–MS/MS and UPLC–MS/MS for the multi-residue analysis of quinolones, penicillins and cephalosporins in cow milk, and validation according to the regulation 2002/657/EC

Abstract: The aim of this study was to develop and validate an analytical method to simultaneously determine European Union-regulated ȕ-lactams (penicillins and cephalosporins) and quinolones in cow milk. The procedure involves a new solid phase extraction (SPE) to clean-up and pre-concentrate the three series of antibiotics before analysis by liquid chromatography-tandem mass spectrometry (LC-MS/MS) and ultrahigh-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). LC-MS/MS and UPLC-MS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 28 publications
1
66
1
Order By: Relevance
“…A previously described sample treatment procedure [20] was applied to milk samples. Thus, to 2 g of milk, 2 mL of Milli-Q water and 0.5 mL of phosphate solution (0.1 mol L −1 at pH 10) were added.…”
Section: Sample Treatment and Clean-up (Spe)mentioning
confidence: 99%
“…A previously described sample treatment procedure [20] was applied to milk samples. Thus, to 2 g of milk, 2 mL of Milli-Q water and 0.5 mL of phosphate solution (0.1 mol L −1 at pH 10) were added.…”
Section: Sample Treatment and Clean-up (Spe)mentioning
confidence: 99%
“…In order to improve the milk quality and healthiness, it should be free of every physical, biological and chemical contaminations. For instance, different kinds of antibiotics, most typically the Benzylpenicillin (2), which can basically cause numerous problems to the dairy industry (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, LC-MS or LC/MS/MS are the preferred techniques in the determination of ␤-lactams residues. A number of authors have reported multiresidue methods for the determination of ␤-lactams in animal tissues or milk [6,[9][10][11][12][13][14][15][16][17], but only a few of these methods include some cephalosporins as targets of study [9][10][11]16,17].…”
Section: Introductionmentioning
confidence: 99%